Fetal programming in beef cattle: isotopic, metabolomic and phenotypic effects - Schalch Junior, Fernando José (2022)
With the growing population, technological and productive advances are prerequisites for the supply of food to be able to meet the demand. In this context, approaches evaluating the prenatal nutritional effects on productive and reproductive performance, metabolism, meat production and muscle development in cattle have been studied in order to optimize the productive cycle of the species. Thus, this thesis aimed to evaluate the phenotypes, isotopic nitrogen fractionation and the blood plasma metabolome of cows and calves submitted to different prenatal nutritional stimuli. In order to carry out these experiments, 126 Nellore cows were used, which were divided equally into three different nutritional approaches during pregnancy (NP, PP and FP). The NP treatment (control) received only mineral supplementation (0.03% of body weight) throughout pregnancy; the PP treatment received mineral supplementation (0.03% of body weight) during the first and second third of pregnancy and protein-energy mineral supplementation during the final third of pregnancy (0.3% of body weight); and the FP treatment received protein-energy mineral supplementation (0.3% of body weight) throughout pregnancy. From calving, the treatments were stopped and all the animals (cows and calves) were submitted to the same environmental, nutritional and sanitary conditions. During the gestational period and after the calving, the phenotypes and blood samples of the cow-calf pair were collected to analyze the effects of the different nutritional strategies applied. In the first chapter, the evaluation of the phenotypic effects caused by prenatal nutrition in cows (body weight, body condition score, subcutaneous fat thickness) and in calves (body weight of males and females) was carried out. In this chapter it was possible to observe that nutrition altered body weight, body condition score and fat thickness of cows and had an influence on the weight of male calves at birth and over time. However, the different maternal stimuli had no effect on the body weight of female offspring. In chapter 2, the fractionation of nitrogen (15N/14N) in the blood plasma of 15 cows (randomly selected) was evaluated at the beginning, at the end of gestation and postpartum and in the progeny at 30 and 180 days of age. Initially, the cows did not show differences in the abundance of 15N, however, after receiving the different treatments, differences in the isotopic nitrogen fractionation were observed between the groups in the pre-calving and post-calving periods. At 30 days of age of calves, effects of prenatal nutrition on isotopic nitrogen levels were observed, but this was not repeated at 180 days of age. In the third chapter, the blood plasma metabolome of the dams at the beginning of pregnancy and prepartum, and the plasma metabolome of the calves at 30 days of age were evaluated. We found metabolic effects in cows in all analyzed collections and some metabolites differentially expressed in calves. In addition, we also found evidence of epigenetic effects related to histidine and beta-alanine metabolism. In short, this thesis brings new approaches and results to the field of prenatal nutrition in beef cattle, which can significantly contribute to the understanding of part of the phenotypic and molecular responses still discussed in the literature.